Genotype characterization of Epstein–Barr virus among adults living with human immunodeficiency virus in Ethiopia - Zealiyas, Kidist; Teshome, Seifegebriel; Haile, Aklilu Feleke; Weigel, Christoph; Alemu, Ayinalem; Amogne, Wondwossen; Yimer, Getnet; Abebe, Tamrat; Berhe, Nega; Ahmed, Elshafa Hassan; Baiocchi, Robert A. (Frontiers in Microbiology, 2023)
Background Epstein–Barr virus (EBV) is a human lymphotropic herpesvirus with a causative agent in cancer. There are two genotypes of EBV (EBV genotype 1 and EBV genotype 2) that have been shown to infect humans. This study aimed to characterize the EBV genotype among people with human immunodeficiency virus (PWH) and HIV-negative individuals in Ethiopia. Methods DNA was extracted from peripheral blood mononuclear cells (PBMCs). Conventional polymerase chain reaction (cPCR) targeting EBNA3C genes was performed for genotyping. A quantitative real-time PCR (q-PCR) assay for EBV DNA (EBNA1 ORF) detection and viral load quantification was performed. Statistical significance was determined at a value of p < 0.05. Result In this study, 155 EBV-seropositive individuals were enrolled, including 128 PWH and 27 HIV-negative individuals. Among PWH, EBV genotype 1 was the most prevalent (105/128, 82.0%) genotype, followed by EBV genotype 2 (17/128, 13.3%), and mixed infection (6/128, 4.7%). In PWH, the median log10 of EBV viral load was 4.23 copies/ml [interquartile range (IQR): 3.76–4.46], whereas it was 3.84 copies/ml (IQR: 3.74–4.02) in the HIV-negative group. The EBV viral load in PWH was significantly higher than that in HIV-negative individuals (value of p = 0.004). In PWH, the median log10 of EBV viral load was 4.25 copies/ml (IQR: 3.83–4.47) in EBV genotype 1 and higher than EBV genotype 2 and mixed infection (p = 0.032). Conclusion In Ethiopia, EBV genotype 1 was found to be the most predominant genotype, followed by EBV genotype 2. Understanding the genotype characterization of EBV in PWH is essential for developing new and innovative strategies for preventing and treating EBV-related complications in this population.